Manajemen Pengembangan Kurikulum Berbasis Pesantren - Nurkholis Nurkholis; Achadi Budi Santosa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The educational curriculum at Islamic boarding schools has an important contribution as an effort to develop an education system based on local wisdom. The development of the Islamic boarding school curriculum is expected to be able to provide a distinctive color in the dynamics of national education. This qualitative research uses a narrative literature review approach that originates from various manuscripts that discuss education, especially Islamic boarding schools. Data collection techniques were carried out through document review and confirmed through random observations at several sample pesantren. Data analysis used inductive techniques, starting with grouping data according to the theme, giving meaning to each part, and then summarizing descriptively. The results of the study show that the development of the Islamic boarding school curriculum still maintains a distinctive style, even though it is realized that the classical education model is difficult not to be influenced by modern education. Humanistic education is carried out as an effort to help students find their potential, so that they can develop naturally. Reconstruction of the curriculum is needed to realize social learning objectives, so that students are ready to live in society. This curriculum emphasizes the principles of cooperation and mutual respect in the learning process, so that a conducive learning atmosphere is created.